Towards a new sophistication in vocabulary assessment. (January 2023) - Read, John
Published work on vocabulary assessment has grown substantially in the last 10 years, but it is still somewhat outside the mainstream of the field. There has been a recent call for those developing vocabulary tests to apply professional standards to their work, especially in validating their instruments for specified purposes before releasing them for widespread use. A great deal of work on vocabulary assessment can be seen in terms of the somewhat problematic distinction between breadth and depth of vocabulary knowledge. Breadth refers to assessing vocabulary size, based on a large sample of words from a frequency list. New research is raising questions about the suitability of word frequency norms derived from large corpora, the choice of the word family as the unit of analysis, the selection of appropriate test formats, and the role of guessing in test-taker performance. Depth of knowledge goes beyond the basic form-meaning link to consider other aspects of word knowledge. The concept of word association has played a dominant role in the design of such tests, but there is a need to create test formats to assess knowledge of word parts as well as a range of multi-word items apart from collocation.